Borderline Dysplasia with Acetabular Retroversion: Key Findings from a Large Hip Arthroscopy Study Group. Issue 7 (31st July 2020) - Kivlan, Benjamin; Nho, Shane; Wolff, Andrew; Salvo, John; Christoforetti, John; Ellis, Thomas; Carreira, Dominic; Matsuda, Dean
Objectives: The radiographic crossover sign (COS) is an indicator of acetabular retroversion, classically representing anterosuperior overcoverage often treated with acetabuloplasty which could exacerbate acetabular hypovolemia in dysplasia. No prior study has investigated the prevalence of acetabular retroversion in patients with dysplasia undergoing hip arthroscopy, acetabuloplasty rates, and outcomes in this setting. Study objectives are to report the prevalence of acetabular retroversion in dysplasia, the influence of the COS on arthroscopic acetabuloplasty rates, and relative outcomes compared with control groups. Methods: A retrospective cohort study was performed from a prospectively collected multi-center database. Patients undergoing isolated hip arthroscopic surgery were assigned to dysplasia (lateral center-edge angle (LCEA) ≤ 25°) or one of two control groups: normal(LCEA 26-38°), or pincer femoroacetabular impingement (FAI)(LCEA ≥ 39°). The prevalence of COS and acetabuloplasty rates between and within study and control groups were compared (Chi square analysis). Minimum 2 year outcomes utilizing iHOT-12 were compared (analysis of variance). Results: Of 401 study patients, 64 (16%) comprised the dysplasia group, 273 (68%) normal group, and 64 (16%) pincer group. Mean LCEAs were 22.3°, 31.5°, and 42.4°, respectively (p<0.001). COS prevalence was similar between groups at 31%, 26%, and 33%, respectively (p=0.873). Acetabuloplasty rates were dependent on the amount of acetabular coverage with lowered rate in the dysplasia group(40%) and increasing rates in the normal(52%) and the pincer(90%) groups (p=0.013). Post-operative iHOT-12 scores improved in all groups (68, 74, and 77, respectively, p=0.222). Patients with a COS plus rendered acetabuloplasty reported similar scores that improved to 77, 74, and 79, respectively, (p=0.949). Patients with dysplasia with COS averaged 73.1(SD 23.3) iHOT-12 score compared to 67.1(SD: 28.7) for the patients with dysplasia without COS (p=0.466). Within the dysplasia with COS subgroup, there was no significant difference in iHOT-12 scores between the group with acetabuloplasty (77.0;SD:17.1) and without acetabuloplasty (70.4;SD:27.4, p=0.580). Conclusion: Acetabular retroversion occurs with similar prevalence in borderline dysplasia compared with non-dysplastic hips undergoing hip arthroscopy but with lower acetabuloplasty rates not influenced by the COS. Arthroscopic outcomes of dysplasia with retroversion are similarly successful and comparable with those of dysplasia and non-dysplastic hips. Although infrequently performed, acetabuloplasty did not compromise outcomes in dysplasia with retroversion.